(untitled) (The Batuk, 2022)
This study is conducted to investigate the transformational leadership (TL) dimensions of head teachers of community schools. To fulfill the objective, the study adopted quantitative research design followed by the survey method. The data obtained from 36 head teachers working in the various community secondary schools in Lalitpur district was processed using SSPS and then analyzed employing descriptive statistics. The findings concluded that the head teachers are practicing transformational leadership styles properly. It contributes to the development of an educational institution by encouraging head teachers to practice transformational leadership. It helps to ensure teachers’ commitment leading to a more effective and viable school environment and helps to establish cordial relationship among the stakeholders for academic enhancement. This study also contributes to school leaders to ensure better academic performance, commitment, and demonstrate their transformational and pedagogical leadership capacity.